Supervisory Risk Assessment in a Basel Environment:The Stress Testing of Banks in Botswana - Mathame, Thobo (Department of Finance and Tax, 2019)
The study uses stress testing to determine the need, if any, for additional capital and/or provisioning for commercial banks in Botswana. The aim is to probe the use of supervisory stress testing as a mitigating factor to some concerns that have been raised with the Basel capital adequacy ratio (CAR) following the 2007-9 global financial crisis. During the crisis, some financial institutions failed or required some form of government assistance, amid having met the minimum CAR requirements prior to the crisis. This led to increased public scrutiny and a loss of confidence in financial regulation. As a result, some scholars have argued that the Basel capital framework is not sufficient as a measure of capital adequacy and as such advocate for the adoption of stress testing to overcome the shortcomings. Specific reference is often made to the success of the subsequent SCAP (US) and CEBS (EU) stress tests that are conceived to have helped restore public confidence as they revealed several oversight loopholes in the existing Basel methodology for the determination of adequate capital for financial institutions. In this regard, this paper considers the context of Botswana, where, even though banks withstood the financial crisis with a relatively strong stance, the economy remains concentrated with heavy dependence on the mining sector. This increases macroeconomic vulnerability and banking sector risks and hence intensifies the need to ensure that banks have sufficient capital holdings at all times. The study adopts an accounting-based approach to stress testing by applying shocks for credit, interest rate, foreign exchange and liquidity risks with the CAR as the main metric. A combined scenario stress test revealed that a collective change in provisions, NPLs, interest rate and exchange rate, that resulted in a decline in CAR from 19.4 to 18.6 post-shock. The available capital remains adequate even following assumed stress conditions. However, the stress test has revealed weaknesses in credit risk and foreign exchange risk as some banks’ capital adequacy fell below the 15 percent minimum. Furthermore, the scenario analysis showed the need for a P22 million capital injection into the banking system, should the tested scenarios occur. As far as can be reasonably established, this kind of study has not been published before for Botswana. As such, this paper lays groundwork for future studies particularly relating to the formulation of scenarios that can better reflect the risk profile of the Botswana banking system.